Membangun Kepuasan Mahasiswa Pengguna Laboratorium Komputer - Lukman Hidayat; Mumuh Mulyana; Marwan Effendy (JAS-PT (Jurnal Analisis Sistem Pendidikan Tinggi Indonesia), 2017)
The purpose of this research is to analyze the service quality factors that influence on student satisfaction when they use Computer Laboratory. The study was conducted at the STIE Kesatuan Laboratory of Computer with 100 students as the respondents. Data were analyzed using Structural Equation Model approach. Results showed variable Physical Evidence, Empathy, Security, Reliability and Responsiveness able to explain the variability construct of Service Quality strongly by 69.53%. The fifth element of service quality has a positive and significant relationship to the Student Satisfaction Keywords: Service Quality,Laboratory of Computer, Student Satisfaction